Voice(s) in Action: Using the Listening Guide in Observational Research - Bright, Felicity; Kayes, NM; Worrall, L; McPherson, KM (The 10th International Congress of Qualitative Inquiry, 2014)
Patient engagement, a hot topic in the healthcare sector, involves not just the patient but staff and healthcare structures. Our study focuses on how rehabilitation providers engage people with communication difficulties in stroke rehabilitation. We use the Voice-Centered Relational Method, including the Listening Guide, to analyze interview and observational data, paying close attention to how participants speak of themselves and of others. While the Listening Guide is usually used with interview data, we use it also with observational data, considering how people represent themselves, and how they speak of themselves and others, within face-to-face clinical encounters. This methodological poster will demonstrate how we are applying the Listening Guide with observational data. We suggest bringing together interview and observational data can illuminate the multiplicity of voices evident within the practice of healthcare providers, and can provide an understanding of how and why they work in the ways they do.